KEBIJAKAN NASIONAL TERHADAP PEMBANGUNAN BERWAWASAN LINGKUNGAN - Poerwanti Hadi Pratiwi * (Pendidikan Sosiologi FIS UNY, 2008)
This article is going to discuss about national policy in the development of environment concept, or known as Ecodevelopment. The focus of this article will be more illuminated on the decreasing of causal factor of development in Indonesia. Ecodevelopment strategy consist of especially elements are community different from others, specific cultural values, live in specific territories, and specific resources too. Because of ecodevelopment strategy goals are reform and develop specific conditions, not create